Oxidative hydrolysis of aliphatic bromoalkenes: scope study and reactivity insights - Jadhav, Amol P.; Legault, Claude Y. (Beilstein Journal of Organic Chemistry, 2024)
We have developed an operationally simple method for the synthesis of dialkyl α-bromoketones from bromoalkenes by utilizing a hypervalent iodine-catalyzed oxidative hydrolysis reaction. This catalytic process provides both symmetrical and unsymmetrical dialkyl bromoketones with moderate yields across a broad range of bromoalkene substrates. Our studies also reveal the formation of Ritter-type side products by an alternative reaction pathway.
Keywords: bromoalkenes; bromoketones; hypervalent iodine; oxidative hydrolysis; Ritter-type